2021
DOI: 10.21203/rs.3.rs-723001/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperexcitability in Older Adults with Elevated Beta-Amyloid

Abstract: Background: Growing evidence links beta-amyloid (Aβ) and neuronal hyperexcitability in preclinical mouse models of Alzheimer’s disease (AD). The aim of this study was to compare neuronal excitability between cognitively normal amyloid positive (CNAβ+) and those without elevated amyloid (CNAβ-) older adults. We hypothesized CNAβ+ participants would show hyperexcitability, indexed by greater peak P3 event-related potential peak amplitude, shorter peak latency, and changes in event-related power, compared to CNAβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…It is presently challenging to make comparisons with clinical data, as early-stage hyperactivation in human AD and its effect on E/MEG spectra are yet to be fully explored. Recent studies, however, have found increases in alpha power in healthy Aβ-burdened and amnesic older adults specifically in the parietal region [47,49], the region which our simulations predict to show the greatest early alpha power increase. Moreover, there is preliminary evidence for hyperactivation in the default-mode network in early-stage AD patients [45].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is presently challenging to make comparisons with clinical data, as early-stage hyperactivation in human AD and its effect on E/MEG spectra are yet to be fully explored. Recent studies, however, have found increases in alpha power in healthy Aβ-burdened and amnesic older adults specifically in the parietal region [47,49], the region which our simulations predict to show the greatest early alpha power increase. Moreover, there is preliminary evidence for hyperactivation in the default-mode network in early-stage AD patients [45].…”
Section: Discussioncontrasting
confidence: 72%
“…Recent findings indicate that oscillatory slowing is prominent in frontal and parietal regions and correlates with subjective cognitive decline [47] and clinical tests for dementia [48]. Moreover, momentary increases in alpha power have been observed for early-stage AD patients [45] and amnesic [47], Aβ-burdened healthy adults [49]. Hyperactivity induced by Aβ and damage-related compensatory mechanisms may be the cause of such early-stage power increases.…”
Section: Introductionmentioning
confidence: 99%